موقف المكناسي من العلماء في كتابه "اتحاف ذوي الاستحقاق" - خلف، سندس محمد (الجامعة المستنصرية - كلية التربية الأساسية, 2020)
إن ألفية ابن مالك المتوفي (679هـ) من الشروحات المهمة التي حازت على مكانة كبيرة بين العلماء؛ لذا شرحها عدد كبير من العلماء، وجاء هذا البحث لبيان موقف المكناسي المتوفي (919هـ) من العلماء في كتابة اتحاف ذوي الاستحقاق، الذي يعد شرحا وتعليقا على كتابي المرادي والشاطبي اللذين شرحا الفية ابن مالك، واستعمل الرموز لأسماء العلماء فرمز للمرادي بـ(د) والشاطبي بـ(ق) في شرحه. ثم شرح المكناسي ابيات الالفية شرحا مفصلا، وصرح بأسماء الكتب والعلماء الذين نقل عنهم. وفي شرحه هذا وافق العلماء في مسائل كثيرة، أما رده عليهم فكان قليلا. وأكثر من ذكر التعقيبات على متن الألفية. وأشار الي المسائل الخلافية بين البصريين والكوفيين بشكل قليل، ولم يصرح بتأييد أحدهما.
Alfiah Ibn Malik (679 AH) is one of the important explanations that has a great position among scholars. Therefore, a large number of scholars explained it, and this research came to explain the position of Al-Maknassi (919 AH) from the scholars in his book enrichment of those with merit, which is an explanation and commentary on Al-Muradi and Al-Shatby, who explained Alfiah Ibn Malik, and used the symbols for the names of scholars, so he symbolized the Murady with (D) and Al-Shatby with (S) in his explanation. Then Al-Meknesi explained the verses of the Alfiah in detail and stated the names of the books and scholars who were quoted from them. In his explanation, he agreed with the scholars on many issues, and his response to them was little, and he added many comments on it. He referred to the controversial issues between the Basri and the Kufic in a brief way, and he did not declare support for either of them
Keywords: المكناسي، محمد بن أحمد بن محمد، ت. 919 هـ. -- كتاب "اتحاف ذوي الاستحقاق" -- ابن مالك، محمد بن عبدالله، ت. 679 هـ